2008
DOI: 10.1161/atvbaha.108.176008
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Procoagulant Activity Dictates Clot Structure and Stability as a Function of Distance From the Cell Surface

Abstract: Background-Thrombin concentration modulates fibrin structure and fibrin structure modulates clot stability; however, the impact of localized, cell surface-driven in situ thrombin generation on fibrin structure and stability has not previously been evaluated. Methods and Results-Human fibroblasts were incubated with factors Xa, Va, prothrombin and fibrinogen, or plasma.Fibrin formation, structure, and lysis were examined using laser scanning confocal microscopy and transmission electron microscopy. In situ thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 44 publications
7
93
0
Order By: Relevance
“…Our results confirmed previous work performed by Jerome et al [17]. Other authors have found that the clot organization was related to the thrombin generated on the cell surface, and when they added exogenous thrombin no change was observed in the fibrin morphology [19].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results confirmed previous work performed by Jerome et al [17]. Other authors have found that the clot organization was related to the thrombin generated on the cell surface, and when they added exogenous thrombin no change was observed in the fibrin morphology [19].…”
Section: Resultssupporting
confidence: 93%
“…This fibers arrangement proximal to the cells is lost in the presence of antibodies against α v and/or β 3 integrin subunits [17] or the synthetic RGD peptide [18]. In contrast, other studies have concluded that the fibrin structure near the cell surface was related to the thrombin generated on the cells surface, and in their experiments the addition of RGD peptide did not affect the fibrin structure [19,20]. They did not add antibodies against the integrin subunits that would be more conclusive.…”
Section: Introductionmentioning
confidence: 96%
“…29,30 We note in this context that the fXIII Leu34 variant, which has been identified as a protective trait in thrombotic disorders, produces similar alterations in fibrin structure as high levels of ␥Ј fibrin. 29 In vitro experiments with purified fibrinogen suggest that an increased rate of thrombin generation, as probably occurs in FV Leiden carriers, may override the biochemical differences between the structures of Ala312 and Thr312 fibrin, or ␥A/␥A and ␥Ј/␥A fibrin, [31][32][33][34] providing a theoretical explanation how the FV Leiden mutation might mitigate the risk conferred by FGA-H1/FGG-H2.…”
Section: Discussionmentioning
confidence: 99%
“…14 Fibrin structure is influenced by platelets. [15][16][17][18] The platelet surface is a regulator of procoagulant activity and local thrombin concentration, parameters that have been shown to dictate clot structure. 18 Platelets interact directly with fibrin by the ␣IIb␤3 integrin that alters fibrin structure and susceptibility to lysis.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The platelet surface is a regulator of procoagulant activity and local thrombin concentration, parameters that have been shown to dictate clot structure. 18 Platelets interact directly with fibrin by the ␣IIb␤3 integrin that alters fibrin structure and susceptibility to lysis. [15][16][17] When stimulated, platelets release polyphosphate (polyP) from the dense granules.…”
Section: Introductionmentioning
confidence: 99%